A boy and his AAC team: building instructional competence across team members. (3rd July 2018) - Snodgrass, Melinda R.; Meadan, Hedda
Abstract: Families and education professionals face unique challenges when working together to support augmentative and alternative communication (AAC) for a child who does not use speech and has only prelinguistic forms of communication. For this study, a family-school team was provided with a specially designed support package comprising training and one-on-one coaching in evidence-based instructional strategies. As part of a larger mixed methods investigation, a single-case experimental design was conducted to explore the effectiveness of the support package on facilitating team members' competence in AAC instruction and communication. In the case reported here, the support package improved instructional competence across all team members, which led to small, positive changes in the child's communication using AAC. However, it was not sufficient for overcoming contextual barriers and supporting adults' ongoing instructional adjustment to the level necessary to promote the child's independent communication via AAC. Implications of these findings for both practice and research are discussed.